Effect of Aeromonas Hydrofila on Interleukin 10 Gene Expression of Liver, Spleen and Muscle Tissue in Common Carp Fish (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The study was conducted in the laboratory of fish belonging to the Department of Animal Production at the Technical College of Musayyib for the period from February 23 to March 16/2019 , the experiment included four treatments, namely control treatment (t1) and salt group (t2) and live bacteria group (t3) and killed bacteria group (t4), by 20 A common carp Caprinus Carpio fish per treatment.the aim of the study was to identify the effect of bacterial infection in the gene expression of the gene IL-10 and compare this expression between three tissues, namely liver, spleen and muscle tissue .Regarding the gene expression of the IL-10 gene, the treatment of live bacteria (t3) showed the highest gene expression compared to the rest of the liver, but it But it made little difference with the B-actin gene (23.71). In the spleen, the gene expression of the IL-10 gene was highest in the fourth treatment (t4) (23.29), but it was lower than the comparison gene B-actin (25.76) for the same treatment. In muscular tissue, the gene expression of IL-10 was higher in the control treatment (t1) compared to the rest of the treatments, but Gene expression was the least in the comparison gene β-actin compared to the rest of the treatments. Regarding the relative expression of the IL-10 gene (relative to the comparison gene and control treatment) in the liver, the live bacterial treatment (t3) recorded the highest relative expression of the IL-10 gene (728.6) followed by the treatment of the killed bacteria (t4) (22.86) by a highly difference from Salt (t2) (1.16)  . in the spleen, the treatment of the bacteria killed (t4) was the highest relative expression (2112.8) by a highly difference with the second and third treatments (15.5,3.09 respectively). In muscle tissue,  the relative expression of the IL-10 gene in second, third and fourth treatments were lowest than in the control treatment relative to the β-actin gene. We conclude that the highest expression of the IL-10 gene appeared in the liver when bacterial infection occurred and was not the case in the spleen and muscle tissue.